2020
DOI: 10.3390/cancers12082003
|View full text |Cite
|
Sign up to set email alerts
|

Methylation Patterns and Chromatin Accessibility in Neuroendocrine Lung Cancer

Abstract: Lung cancer is the worldwide leading cause of death from cancer. Epigenetic modifications such as methylation and changes in chromatin accessibility are major gene regulatory mechanisms involved in tumorigenesis and cellular lineage commitment. We aimed to characterize these processes in the context of neuroendocrine (NE) lung cancer. Illumina 450K DNA methylation data were collected for 1407 lung cancers including 27 NE tumors. NE differentially methylated regions (NE-DMRs) were identified and correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…For a comprehensive phenotype-level analysis of NSCLC we used isobaric labelling and HiRIEF-LC-MS 8 , 9 with data-dependent acquisition (DDA) reaching an analytical depth of 13,975 identified proteins (gene-centric search, FDR<1%, Figure 1b , Supplementary Table 2 ). In addition to MS-data, mutation analysis for cancer-associated genes was performed by panel sequencing (n=370 genes), furthermore genome-wide methylation and mRNA-level data were available for most samples 10 12 ( Supplementary Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For a comprehensive phenotype-level analysis of NSCLC we used isobaric labelling and HiRIEF-LC-MS 8 , 9 with data-dependent acquisition (DDA) reaching an analytical depth of 13,975 identified proteins (gene-centric search, FDR<1%, Figure 1b , Supplementary Table 2 ). In addition to MS-data, mutation analysis for cancer-associated genes was performed by panel sequencing (n=370 genes), furthermore genome-wide methylation and mRNA-level data were available for most samples 10 12 ( Supplementary Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The early-stage cohort (also referred to as the “discovery cohort”) comprised resected lung cancer tumor samples from a total of 192 patients with operable lung cancer that were surgically treated at the Skåne University Hospital in Lund, Sweden. The samples were collected as described in previous studies 10 12 . The late-stage cohort comprised biopsy material from inoperable lung cancer (84 samples).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, Li et al have demonstrated that the progressive loss of histone H4 acetylation at lysine16 (H4KA16) and trimethylation at lysine 20 (H4KM20) from low to high grade lung neuroendocrine tumors reflects the degree of differentiation and proliferative activity (48). Also methylation patterns have inspired interest because of their correlation with gene expression in lung neuroendocrine cancers (49).…”
Section: Molecular Characteristics Of Lcnecmentioning
confidence: 99%